Continuous glucose monitoring to track metabolic changes in youths with cystic fibrosis before and after initiation of elexacaftor/tezacaftor/ivacaftor therapy - Alfonso Galderisi; Hadija Marchiori; Laurence Weiss; Alix Besançon; Nathalie Stremler; Aline Lustre; Djouher Sahki; Anne-Sophie Bonnel; Isabelle Sermet-Gaudelus; Marianne Alison; Baptiste Arnouat; Melissande Baravalle; et al. (The Journal of Clinical Endocrinology & Metabolism, 2026)
Abstract Introduction Glucose tolerance abnormalities can be detected in preschool and school-age children with cystic fibrosis. There is limited data on the impact of CFTR modulator elexacaftor/tezacaftor/ivacaftor (ETI) on their trajectories. We examined CGM metrics before and after ETI initiation across different pediatric age groups. Methods We included participants from the French MODUL-CF real world study aged 2-18 years with at least 24 hours of CGM data before initiation of ETI and a 2nd CGM 12±3 months following ETI start. The cohort was stratified in 3 groups based on the age at ETI initiation: <6, 6-12 and >12 years. CGM derived glucose metrics were compared before and after ETI. Results 98 patients with CF were enrolled, including 13 preschool children, 55 school age children and 32 adolescents. At baseline, participants displayed a time in tight glucose range (TITR) of 89.8%(84.1, 93.4) with 34% of the whole cohort spending >10% of time>140mg/dL (TA140). Following treatment, TITR increased of ∼2%(+1.8[-1.8, +6.0]%) (p=0.004). This was associated with a 0.4% reduction of mild-hyperglycemia (>140mg/dL) and a lower CV (21.5%(19.0, 24.7) vs 19.6%(17.0, 22.6), p<0.001). Those with TA140≤10% at baseline displayed greater weight gain and improvement of lung function respect to the group with TA140>10%. Conclusion ETI is associated with improvement of CGM glucose in children and adolescents with CF. TA140 before ETI initiation may impact the trajectory of clinically relevant outcomes.